Ethical approaches to abortion; a case study - SH Eslami (JRI, 2005)
In his paper, the author tries to deal with one of the most controversial ethical problems of the modern time from a moral point of view; abortion. Is abortion moral? and can it be justified in any situation? Or it cannot be justified in any case? There are four main ethical approaches to abortion: First,a conservative approach, second, a liberal, third, a moderate, and fourth, a femi-nistic one. None of these approaches seem to be able to justify various kinds of abortion. We need to deal with every case separately and try to assess its morality. Accepting this view, the author tries to face abortion due to rape and he argues that this kind of abortion may rest its reasons on four principles: Autonomy, justice principles, self-defense, and the responsibility of society toward the pregnant woman as a victim of violence and rape. According to these prin-ciples, if a woman is raped and becomes pregnant, it is her personal choice to continue her pregnancy or abort it. Then the author goes into some jurisprudential details from an Islamic perspective and tries to defend his position by citing some famous Islamic legal decisions, or "Fatwa"s.
Keywords: Abortion, Rape, Applied ethics, Ethical decision, Ethics